Effect of an Educational Intervention on the Utilization of Maternal Healthcare Services for High-Risk Obstetric Clients, Systematic Review - Osoro, Epony Nyakong’anyi; Tenambergen , Wanja Mwaura; Njoroge, Kezia (International Journal of Professional Practice, 2024)
This study aims to investigate how health systems can be strengthened through timely referral of obstetric patients. In many Low and Middle-Income Countries (LMICs), maternal and newborn mortality and morbidity outcomes continue to be major health issues. Most of the deaths occur in sub-Saharan Africa and South Asia where access to maternal and newborn health care is a challenge. Strengthening health systems aims at increasing access to vital services such as maternal and neonatal care to improve health outcomes. The broad objective of this systematic review was to determine the level of effectiveness of education interventions aimed at improving timely referral of obstetric patients to higher-level healthcare facilities, with the goal of strengthening health systems and improving maternal and new-born healthcare outcomes. This study adopts a systematic review of the meta-analysis approach. For articles, six electronic databases; namely, Science Direct, Scopus, EMBASE, PubMed, PLOS One, and Google Scholar were searched. The target population was publications on obstetric patients in low- and middle-income countries. Data were analysed using meta-analysis techniques. The results of the review indicated that education and training intervention had a statistically significant impact on five outcomes; namely, maternal mortality (p=0.05), service utilization (p=0.001), number of emergency referrals (p=0.00001), and referral time (0.05), though the margin was small in the latter. These outcomes were marked with significant improvement, following the implementation of the treatment of high risk obstetric patients. However, there was lack of meaningful impact of the intervention on neonatal mortality (p=0.80). The study concluded that timely referral can be enhanced by implementing education interventions such as training expectant women and healthcare providers.